Clinical Subtypes of Dementia with Lewy Bodies Based on the Initial Clinical Presentation. - Morenas-Rodriguez, Estrella; Sala, Isabel; Subirana, Andrea; Pascual-Goñi, Elba; Sánchez-Saudinós, Ma Belén; Alcolea, Daniel; Illán-Gala, Ignacio; Carmona-Iragui, María; Ribosa-Nogué, Roser; Camacho, Valle; Blesa, Rafael; Fortea, Juan; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Dementia with Lewy bodies (DLB) is a heterogeneous disease in which clinical presentation, symptoms, and evolution widely varies between patients. OBJECTIVE: To investigate the existence of clinical subtypes in DLB based on the initial clinical presentation. METHODS: 81 patients with a clinical diagnosis of probable DLB were consecutively included. All patients underwent a neurological evaluation including a structured questionnaire about neuropsychiatric symptoms and sleep, an assessment of motor impairment (Unified Parkinson Disease Rating Scale subscale III), and a formal neuropsychological evaluation. Onset of core symptoms (hallucinations, parkinsonism, and fluctuations) and dementia were systematically reviewed from medical records. We applied a K-means clustering method based on the initial clinical presentation. RESULTS: Cluster analysis yielded three different groups. Patients in cluster I (cognitive-predominant, n = 46) presented more frequently with cognitive symptoms (95.7%, n = 44, p < 0.001), and showed a longer duration from onset to DLB diagnosis (p < 0.001) than the other clusters. Patients in cluster II (neuropsychiatric-predominant, n = 22) were older at disease onset (78.1±5 versus 73.6±6.1 and 73.6±4.2 in clusters I and III, respectively, both p < 0.01), presented more frequently with psychotic symptoms (77.3%, n = 17), and had a shorter duration until the onset of hallucinations (p < 0.001). Patients in cluster III (parkinsonism-predominant, n = 13) showed a shorter time from onset to presence of parkinsonism (p < 0.001) and dementia (0.008). CONCLUSIONS: Three clinical subtypes of DLB can be defined when considering the differential initial presentations. The proposed subtypes have distinct clinical profiles and progression patterns.

Diagnostic and Prognostic Value of the Combination of Two Measures of Verbal Memory in Mild Cognitive Impairment due to Alzheimer's Disease. - Sala, Isabel; Illán-Gala, Ignacio; Alcolea, Daniel; Sánchez-Saudinós, Ma Belén; Salgado, Sergio Andrés; Morenas-Rodriguez, Estrella; Subirana, Andrea; Videla, Laura; Clarimón, Jordi; Carmona-Iragui, María; Ribosa-Nogué, Roser; Blesa, Rafael; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Episodic memory impairment is the core feature of typical Alzheimer's disease. OBJECTIVE: To evaluate the performance of two commonly used verbal memory tests to detect mild cognitive impairment due to Alzheimer's disease (MCI-AD) and to predict progression to Alzheimer's disease dementia (AD-d). METHODS: Prospective study of MCI patients in a tertiary memory disorder unit. Patients underwent an extensive neuropsychological battery including two tests of declarative verbal memory: The Free and Cued Selective Reminding Test (FCSRT) and the word list learning task from the Consortium to Establish a Registry for Alzheimer's disease (CERAD-WL). Cerebrospinal fluid (CSF) was obtained from all patients and MCI-AD was defined by means of the t-Tau/Aβ1-42 ratio. Logistic regression analyses tested whether the combination of FCSRT and CERAD-WL measures significantly improved the prediction of MCI-AD. Progression to AD-d was analyzed in a Cox regression model. RESULTS: A total of 202 MCI patients with a mean follow-up of 34.2±24.2 months were included and 98 (48.5%) met the criteria for MCI-AD. The combination of FCSRT and CERAD-WL measures improved MCI-AD classification accuracy based on CSF biomarkers. Both tests yielded similar global predictive values (59.9-65.3% and 59.4-62.8% for FCSRT and CERAD-WL, respectively). MCI-AD patients with deficits in both FCSRT and CERAD-WL had a faster progression to AD-d than patients with deficits in only one test. CONCLUSIONS: The combination of FCSRT and CERAD-WL improves the classification of MCI-AD and defines different prognostic profiles. These findings have important implications for clinical practice and the design of clinical trials.

Feasibility of Lumbar Puncture in the Study of Cerebrospinal Fluid Biomarkers for Alzheimer's Disease in Subjects with Down Syndrome. - Carmona-Iragui, María; Santos, Telma; Videla, Sebastián; Fernández, Susana; Benejam, Bessy; Videla, Laura; Alcolea, Daniel; Blennow, Kaj; Blesa, Rafael; Lleo, Alberto; Fortea, Juan (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is the main medical problem in older adults with Down syndrome (DS). Studies of cerebrospinal fluid (CSF) AD biomarkers are limited and the feasibility of lumbar puncture (LP) is controversial in this population. OBJECTIVE: To analyze the frequency of complications after a LP in DS. METHODS: We collected data from 80 adults with DS that underwent a LP within the Down Alzheimer Barcelona Neuroimaging Initiative. Demographics, cognitive status, headache history, and presence of complications after the LP were recorded in every subject. In 53 of them (active group), this information was collected following a semi-structured and validated protocol that actively looks for complications. Other variables related to the LP procedure were also recorded. A telephone interview to the caregiver was performed 5-7 days after the procedure to ask about complications. Data from 27 subjects (clinical practice group), from whom the presence of complications was obtained in a medical follow-up visit within the three months after the LP, were also included. RESULTS: There were no adverse events in 90% of our participants. The most frequent complication was headache (6.25%); only one subject reported a typical post-lumbar puncture headache with moderate severity that required analgesic treatment. Dizziness (3.75%) and back pain (1.25%) were also reported. All the participants that reported complications belonged to the active group. CONCLUSION: LP can be safely performed to study CSF biomarkers in DS. The reported complications are qualitatively similar to the general population, but are less frequently reported, even when actively searched for.

Cerebrospinal Fluid Anti-Amyloid-β Autoantibodies and Amyloid PET in Cerebral Amyloid Angiopathy-Related Inflammation. - Carmona-Iragui, María; Fernández-Arcos, Ana; Alcolea, Daniel; Piazza, Fabrizio; Morenas-Rodriguez, Estrella; Antón-Aguirre, Sofía; Sala, Isabel; Clarimón, Jordi; Dols-Icardo, Oriol; Camacho, Valle; Sampedro, Frederic; Munuera, Josep; et al. (J Alzheimers Dis, 2016)
We report a biomarker and genetic evaluation of four patients with cerebral amyloid angiopathy-related inflammation (CAA-ri) treated with corticosteroids. Patients presented with focal symptomatology and cognitive impairment. MRI revealed cortical microbleeds and asymmetrical hyperintense white matter lesions (WML). Cerebrospinal fluid (CSF) biomarker analyses showed increased anti-Aβ autoantibodies, t-Tau, and p-Tau and decreased Aβ40 and Aβ42. After treatment, focal symptomatology disappeared, and WML and anti-Aβ autoantibodies decreased. The APOEɛ4 allele was overrepresented. Florbetapir-PET showed cortical deposition with lower retention in swollen areas. In the case of suspected CAA-ri, both CSF anti-Aβ autoantibodies levels and Florbetapir-PET could provide highly useful data to guide the correct diagnosis.
Keywords: Aged; Amyloid beta-Peptides; Aniline Compounds; Apolipoproteins E; Autoantibodies; Cerebral Amyloid Angiopathy; Ethylene Glycols; Female; Humans; Magnetic Resonance Imaging; Male; Meningoencephalitis; Peptide Fragments; Positron-Emission Tomography; Statistics, Nonparametric; tau Proteins

Progranulin Protein Levels in Cerebrospinal Fluid in Primary Neurodegenerative Dementias. - Morenas-Rodriguez, Estrella; Cervera-Carles, Laura; Vilaplana, Eduard; Alcolea, Daniel; Carmona-Iragui, María; Dols-Icardo, Oriol; Ribosa-Nogué, Roser; Muñoz-Llahuna, Laia; Sala, Isabel; Belén Sánchez-Saudinós, M; Blesa, Rafael; Clarimón, Jordi; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Progranulin is implicated in frontotemporal dementia (FTD), but its role in other neurodegenerative disorders is unknown. OBJECTIVE: To investigate the levels of progranulin (PGRN) in cerebrospinal fluid (CSF) in different neurodegenerative dementias and their correlation with levels in plasma in cognitively normal subjects. METHODS: We measured PGRN in CSF in 229 patients with amnestic mild cognitive impairment, Alzheimer's disease dementia, sporadic FTD, dementia with Lewy bodies, corticobasal syndrome, or progressive supranuclear palsy. We also measured PGRN in CSF and plasma in 74 cognitively normal individuals. We examined the correlation between PGRN levels in CSF and diagnosis, cortical thickness, genetic factors and other CSF biomarkers. We also investigated the correlation between plasma and CSF levels of PGRN in cognitively normal individuals. RESULTS: CSF levels did not differ across diagnoses or correlate with cortical thickness. Polymorphism rs5848 in GRN influenced CSF PGRN levels, but APOEɛ4 allele did not. Amyloid-β42, t-tau, p-tau, and YKL-40 levels correlated weakly with PGRN in CSF. We found a weak correlation (r = 0.362) between plasma and CSF PGRN levels in cognitively normal individuals. CONCLUSIONS: Our findings do not support a diagnostic value of CSF PGRN in neurodegenerative diseases. Our data confirm that levels of PGRN in plasma do not reflect accurately levels in CSF in cognitively normal controls. These data should be considered in clinical trials aiming to increase PGRN.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Biomarkers; Dementia; Female; Humans; Intercellular Signaling Peptides and Proteins; Male; Middle Aged; Neurodegenerative Diseases; Polymorphism, Single Nucleotide; tau Proteins